NMNAT1 mutations cause Leber congenital amaurosis - Falk, Marni J; Zhang, Qi; Nakamaru-Ogiso, Eiko; Kannabiran, Chitra; Fonseca-Kelly, Zoe; Chakarova, Christina; Audo, Isabelle; Mackay, Donna S; Zeitz, Christina; Borman, Arundhati Dev; Staniszewska, Magdalena; Shukla, Rachna; et al. (Nature genetics, 2012)
Eric Pierce, Xiaowu Gai and colleagues identify mutations in NMNAT1 as a new cause of Leber congenital amaurosis, an early-onset form of retinal degeneration. NMNAT1 encodes an isoform of nicotinamide mononucleotide adenylyltransferase, which is required for nicotinamide adenine dinucleotide (NAD + ) biosynthesis. Leber congenital amaurosis (LCA) is an infantile-onset form of inherited retinal degeneration characterized by severe vision loss 1 , 2 . Two-thirds of LCA cases are caused by mutations in 17 known disease-associated genes 3 (Retinal Information Network (RetNet)). Using exome sequencing we identified a homozygous missense mutation (c.25G>A, p.Val9Met) in NMNAT1 that is likely to be disease causing in two siblings of a consanguineous Pakistani kindred affected by LCA. This mutation segregated with disease in the kindred, including in three other children with LCA. NMNAT1 resides in the previously identified LCA9 locus and encodes the nuclear isoform of nicotinamide mononucleotide adenylyltransferase, a rate-limiting enzyme in nicotinamide adenine dinucleotide (NAD + ) biosynthesis 4 , 5 . Functional studies showed that the p.Val9Met alteration decreased NMNAT1 enzyme activity. Sequencing NMNAT1 in 284 unrelated families with LCA identified 14 rare mutations in 13 additional affected individuals. These results are the first to link an NMNAT isoform to disease in humans and indicate that NMNAT1 mutations cause LCA.